Being well-liked predicts increased use of alcohol but not tobacco in early adolescence. (February 2016) - Van Ryzin, Mark J.; DeLay, Dawn; Dishion, Thomas J.
Abstract: Although substance use has traditionally been linked to peer deviance, a parallel literature has explored the influence of peer social status (being "well-liked"). This literature hypothesizes that adolescents with higher status will anticipate shifts in social norms and modify their behavior earlier and/or more substantially than lower-status students. As substance use becomes more socially acceptable during early-to-mid-adolescence, higher status youth are hypothesized to reflect this shift in norms by accelerating their use more rapidly than lower status youth. Although some evidence exists to support this hypothesis, it has never been evaluated in conjunction with the opposing hypothesis (i.e., that substance use contributes to elevated peer status). In this study, we evaluated reciprocal links between peer status and substance use (i.e., alcohol and tobacco) using 3 years of data from 8 middle schools in the Pacific Northwest. Social network analysis enabled us to model standard network effects along with unique effects for the influence of the network on behavior (i.e., increased substance use as a result of being well-liked) and the influence of behavior on the network (i.e., increased status as a result of substance use). Our results indicated significant bidirectional effects for alcohol use but no significant effects for tobacco use. In other words, being well-liked significantly predicted alcohol use and vice versa, but these processes were not significant for tobacco use. Prevention efforts should consider the dynamics of peer status and peer norms in adolescence with the goal of preventing escalations in problem behavior that can compromise future adjustment. Highlights: Being well-liked may contribute to escalations in substance use during adolescence. Existing research is limited by conventional statistical methods. We used social network analysis to examine links between liking and substance use. We found bidirectional links between liking and use of alcohol but not tobacco. Being well-liked may represent a heretofore unknown risk factor in adolescence.